Hybrid Magnetic Lipid-Based Nanoparticles for Cancer Therapy - Marcela Tavares Luiz; Jessyca Aparecida Paes Dutra; Juliana Santos Rosa Viegas; Jennifer Thayanne Cavalcante de Araújo; Alberto Gomes Tavares Junior; Marlus Chorilli (MDPI AG, 2023)
Cancer is one of the major public health problems worldwide. Despite the advances in cancer therapy, it remains a challenge due to the low specificity of treatment and the development of multidrug resistance mechanisms. To overcome these drawbacks, several drug delivery nanosystems have been investigated, among them, magnetic nanoparticles (MNP), especially superparamagnetic iron oxide nanoparticles (SPION), which have been applied for treating cancer. MNPs have the ability to be guided to the tumor microenvironment through an external applied magnetic field. Furthermore, in the presence of an alternating magnetic field (AMF) this nanocarrier can transform electromagnetic energy in heat (above 42 °C) through Néel and Brown relaxation, which makes it applicable for hyperthermia treatment. However, the low chemical and physical stability of MNPs makes their coating necessary. Thus, lipid-based nanoparticles, especially liposomes, have been used to encapsulate MNPs to improve their stability and enable their use as a cancer treatment. This review addresses the main features that make MNPs applicable for treating cancer and the most recent research in the nanomedicine field using hybrid magnetic lipid-based nanoparticles for this purpose.